Entrepreneurial behavior: A literature review from the scientific production of the GEM project - Mosquera Guerrero, Andrea (2024)
Entrepreneurship has been studied from different approaches worldwide, in which research has been carried out on how people respond to global dynamics at the time of undertaking and the factors that stimulate or slow down the performance index in countries. The objective was to systematically review the literature on entrepreneurship studies from the GEM project. The main findings of the studies of entrepreneurial behavior are associated with the importance of the social, legislative, and political context as the basis of behavioral research. In conclusion, it can be said that entrepreneurial intention is a widely studied variable, a difference in the behavior or action of the undertaking. These issues must be investigated in more depth, a reason for generating knowledge that stimulates new forms of global and individual benefits.